Towards an e-infrastructure for Open Science in Soils Security - da Cruz, Sérgio Manuel Serra; Ceddia, Marcos Bacis; Schmitz, Eber Assis; Rizzo, Gabriel S.; Miranda, Renan C. T.; Cruz, Sabrina O.; Correa, Ana Clara; Klinger, Felipe; Marinho, Elton; Cruz, Pedro Vieira (Anais do Brazilian e-Science Workshop (BreSci), 2018)
Soils Security is a critical and growing global concern. The OpenSoils' objective is to host, connect and share large amounts of curated soil data and knowledge at the Brazilian and South America level. The e-infrastructure consists of several layers of services, a database of soil profiles, a cloud-based computational framework to compute and share soil data integrated with a map visualization tools. OpenSoils is open, elastic, provenance-oriented and lightweight computational e-infrastructure that collects, stores, describes, curates, harmonizes and directs to various soil resource types: large datasets of soils profiles, services/applications, documents, projects and external links. OpenSoils is the first open science-based computational framework of soils security in the literature.